Need Analysis of Learning Material for English for Fashion Students at Ganesha University of Education - Kadek Ristanti Pramudya; Ni Putu Era Marsakawati; Rima Andriani Sari (Universitas Pendidikan Ganesha, 2023)
This study aims to identify the learning materials needed by Fashion Design students at Ganesha University of Education in learning English, through the Needs Analysis approach. The background of this study is the importance of understanding English that is in accordance with the specific needs of the Fashion Design field. This study uses a qualitative method with instruments in the form of open questionnaires, interviews, and document analysis. The subjects of the study consisted of 20 students and 1 lecturer from the Fashion Design department. Data were analyzed using a qualitative descriptive approach involving the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the learning materials needed include: (a) knowledge and skills of English in the context of fashion design; (b) development of language skills relevant to the field; (c) use of learning activities that support multimodal literacy such as video, images, and audio; (d) relevant verbal and non-verbal language skills; and (e) materials and activities that support the improvement of students' vocabulary and grammar. These findings provide implications for the development of a more contextual and specific English curriculum for the Fashion Design field.